Cardiac Tamponade Caused by Cutibacterium acnes: An Updated and Comprehensive Review of the Literature - Ghina Fakhri; Christelle Tayeh; Ghassan Dbaibo; Omar El Sedawy; Nour Abdul Halim; Fadi Bitar; Mariam Arabi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bacterial pericarditis is a critical diagnosis caused by a wide range of organisms including Streptococcus pneumoniae and other anaerobic organisms like Cutibacterium acnes which has been gaining more importance as a causative organism. Cutibacterium species are Gram-positive microaerophilic rods that constitute part of the normal flora of skin and mucosal membranes. The incidence of pericarditis caused by this organism is underreported as it is often dismissed as a skin flora contaminant. However, if left untreated, Cutibacterium acnes can cause pericarditis with serious complications. In this paper, we present a comprehensive review of the literature regarding pericarditis caused by Cutibacterium acnes along with a case presentation from our institution. In our institution, a 20-year-old man with history of atrial septal defect presented with chest pain radiating to the back along with symptoms of upper respiratory tract infection including headaches and myalgia. Electrocardiogram was remarkable for diffuse low-voltage waves. Echocardiography revealed a large pericardial effusion with tamponade features. Pericardiocentesis drained 1.2 L of milky fluid. Pericardial fluid analysis grew Cutibacterium acnes after being cultured for 8 days. The patient received 3 weeks of IV penicillin followed by 3 weeks of oral amoxicillin along with nonsteroidal anti-inflammatory agents and colchicine with no recurrence. Pericarditis caused by Cutibacterium acnes requires a high clinical suspicion since isolation of this organism can be dismissed as a skin flora contaminant. Literature review reveals that this infection may be underdiagnosed and underreported. Prompt diagnosis may lead to timely initiation of antibiotics which can help prevent devastating complications like constrictive pericarditis. Prospective studies are needed to evaluate the true incidence and prevalence of this disease.